Combining Two Powerful Living Polymerizations Using Rationally Designed Bifunctional Initiators for Versatile Synthesis of Conjugated Rod-Coil Block Copolymers - Choi, Hae Nam; Yang, Hee Seong; Park, Songyee; Choi, Tae Lim; Lee, In Hwan (Macromolecules, 2024)
Living polymerization has played a pivotal role in producing conjugated rod-coil block copolymers, offering a means to harness the functions of two distinct materials within nanoscale regions. Nevertheless, the accessibility of a diverse array of such copolymers has been restricted, primarily due to the lack of an efficient synthetic approach. To address this issue, we developed a bifunctional initiator approach that integrates two versatile living polymerizations: atom transfer radical polymerization (ATRP) and Suzuki-Miyaura catalyst-transfer polymerization (SCTP). This approach produces various conjugated rod-coil block copolymers with high precision, molecular weight control, low dispersity, and architecture control. Moreover, the one-pot synthesis of conjugated block copolymers was successfully demonstrated using consecutive photo-ATRP and SCTP. In addition, we systematically investigated the film morphology of the synthesized conjugated block copolymers by addressing the effects of the molecular weight, architecture, and regioisomeric linker units.
Keywords: Atom-transfer radical polymerization; Bifunctional initiators; Catalyst-transfer polymerizations; Conjugated block copolymers; High-precision; Molecular weight control; Nanoscale regions; Rod-coil block copolymer; Suzuki-Miyaura; Synthetic approach